DETERMINING CAPILLARY-PRESSURE CURVE, PORE-SIZE DISTRIBUTION, AND PERMEABILITY FROM INDUCED POLARIZATION OF SHALEY SAND - Tong M.; Wang W.; Jiang Y.; Li L. (My University, 2006)
An appropriate form of induced polarization (IP) acts as a bridge between the structure of a water-saturated core plug and its transport properties. The induced-polarization decay curves of natural rocks can be modeled as a weighted superposition of exponential relaxations. A singular-value decomposition method makes it possible to transform the induced-polarization decay data of the shaley sands into relaxation-time spectrum, defined as plot of weight versus the relaxation-time constant. We measured the induced-polarization decay curves of core samples from a formation of Daqing oil field using a four-electrode method. The decay curves were transformed to relaxation-time spectra that were used to estimate the capillary-pressure curves, the pore-size distribution, and the permeability of the shaley sands. The results show that salinity ranges from 1g/liter to 20g/liter have little effect on the IP relaxation-time spectra. A pseudocapillary pressure curve can be derived from the IP relaxation-time spectrum by matching the pseudocapillary curve with that from HgAir. The best-matching coefficients of the studied cores change slightly for the samples. Defined as the value of pressure at which the injected mercury saturation is 5%, entry pressures of the cores can be estimated well from IP-derived capillary-pressure curves. Pore-size distributions generated from induced polarization and mercury capillary-pressure curves are comparable. Permeability can be predicted from IP measurements in the form of KIP=c · Tm ·, φn, where KIP is the estimated permeability from IP relaxation spectrum in millidarcies (md), φ is the porosity in percentage, and T is average time constant of IP relaxation-time spectra in millis (ms). The constants and exponents from various rock formations are slightly different. © 2006 Society of Exploration Geophysicists.
Keywords: PERMEABILITY; ROCKS; SAND; SINGULAR VALUE DECOMPOSITION; WELL LOGGING